Pengaruh Perbedaan Bangsa Kambing Sannen dan Sapera terhadap Kualitas Susu - Catur Suci Purwati; Sri Sukaryani; Imam Budiharjo; Ludfia Windyasmara (UNIVERSITAS ISLAM LAMONGAN, 2024)
The aim of this research was to determine the physical quality of sapera goat milk at different milking times from the Bamboe Koening Farm Sukoharjo goat farm. There are 10 lactating female sapera goats. Milk samples were taken three times, 100 ml each for each treatment, at Bamboe Koening Farm Sukoharjo. The experimental design used the Independent Student T-Test with 2 treatments and 10 repetitions. The treatments in this research were A, namely morning milking and B, namely afternoon milking. The variables were observed for pH value, specific gravity, fat content, protein content, boiling value and reductase value. The results of this study show that the pH value, fat content and protein content have a real influence, while specific gravity, boiling value, alcohol value and reductase value have no real influence.